2020
DOI: 10.1038/s41598-020-77975-2
|View full text |Cite
|
Sign up to set email alerts
|

Contrast enhanced magnetic resonance imaging highlights neurovasculature changes following experimental traumatic brain injury in the rat

Abstract: Neurovascular injury has been proposed as a universal pathological hallmark of traumatic brain injury (TBI) with molecular markers of angiogenesis and endothelial function associated with injury severity and morbidity. Sex differences in the neurovasculature response post-TBI may contribute to the differences seen in how males and females respond to injury. Steady-state contrast enhanced magnetic resonance imaging (SSCE-MRI) can be used to non-invasively assess the neurovasculature and may be a useful tool in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…2 , Supplementary Table 2 ). In addition to inclusion of both biological sexes, the NIH implemented a related policy in 2016 requiring the use of sex as a biological variable given documented differences in anatomy, physiology, disease presentation, and patient outcomes (Bonkhoff et al 2021 ; Liu et al 2020 ; Wright et al 2020 ). Utilizing 488 subjects in the HCP database, Liu et al observed significant differences in brain structure.…”
Section: Biological Sex Is Largely Reported and Males And Females Are...mentioning
confidence: 99%
“…2 , Supplementary Table 2 ). In addition to inclusion of both biological sexes, the NIH implemented a related policy in 2016 requiring the use of sex as a biological variable given documented differences in anatomy, physiology, disease presentation, and patient outcomes (Bonkhoff et al 2021 ; Liu et al 2020 ; Wright et al 2020 ). Utilizing 488 subjects in the HCP database, Liu et al observed significant differences in brain structure.…”
Section: Biological Sex Is Largely Reported and Males And Females Are...mentioning
confidence: 99%
“…In contrast, only the male rats exhibited worse white matter integrity in the corpus callosum following rmTBI, not in female rats 68 . Furthermore, compared to male rats, female rats had superior vessel density and better neuromotor function following rmTBI 69 . These sexual dimorphisms in TBI responses may be in part due to endocrine-related differences, such as sex hormones 70 .…”
Section: Discussionmentioning
confidence: 84%
“… 61 In addition, it cooperates with neurogenesis to promote brain recovery. 62 , 63 Previous studies demonstrated that microvascular density is compromised acutely after TBI. 63 Then, the cerebral capillaries slowly reestablished to baseline levels within 2 weeks.…”
Section: Discussionmentioning
confidence: 99%